1997
DOI: 10.1177/106002809703100511
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone-Induced Agranulocytosis

Abstract: Agranulocytosis secondary to spironolactone is a serious potential adverse effect. Patients with risk factors for developing this adverse effect should be closely monitored since early detection and discontinuation of spironolactone can improve prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Case reports have demonstrated that spironolactone can cause agranulocytosis [ 1 , 2 , 3 ]. Advanced age, hepatic and renal impairment and concurrent medications have all been identified as contributing to the likelihood of this adverse effect.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have demonstrated that spironolactone can cause agranulocytosis [ 1 , 2 , 3 ]. Advanced age, hepatic and renal impairment and concurrent medications have all been identified as contributing to the likelihood of this adverse effect.…”
Section: Discussionmentioning
confidence: 99%